2019
DOI: 10.1002/wnan.1553
|View full text |Cite
|
Sign up to set email alerts
|

From isolated structures to continuous networks: A categorization of cytoskeleton‐based motile engineered biological microstructures

Abstract: As technology at the small scale is advancing, motile engineered microstructures are becoming useful in drug delivery, biomedicine, and lab-on-a-chip devices. However, traditional engineering methods and materials can be inefficient or functionally inadequate for small-scale applications. Increasingly, researchers are turning to the biology of the cytoskeleton, including microtubules, actin filaments, kinesins, dyneins, myosins, and associated proteins, for both inspiration and solutions. They are engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 239 publications
(353 reference statements)
0
14
0
Order By: Relevance
“… 3 10 Several experimental and theoretical model systems have been developed to study networks of cytoskeletal filaments and motor proteins fueled by ATP. 11 13 A remarkable example is the emergent behavior in 2D observed in mixtures of microtubules and kinesin motors arranged in bundles by a depletion agent pioneered by Sanchez et al 12 Internally generated spatiotemporally chaotic flows at the millimeter scale were observed that persisted as long as ATP was available. The 2D networks exhibit a steady state with permanent flow at large scales, while the dynamics is driven by the buckling and elongation of the microtubule bundles due to the activity of the motors on the nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“… 3 10 Several experimental and theoretical model systems have been developed to study networks of cytoskeletal filaments and motor proteins fueled by ATP. 11 13 A remarkable example is the emergent behavior in 2D observed in mixtures of microtubules and kinesin motors arranged in bundles by a depletion agent pioneered by Sanchez et al 12 Internally generated spatiotemporally chaotic flows at the millimeter scale were observed that persisted as long as ATP was available. The 2D networks exhibit a steady state with permanent flow at large scales, while the dynamics is driven by the buckling and elongation of the microtubule bundles due to the activity of the motors on the nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…The first author to suggest that pattern formation in living systems may have a chemical basis was Alan Turing in 1952 [130,129] in the landmark paper The chemical basis of morphogenesis. 1 Turing discovered that a mixture of chemical species that react and diffuse can, in some cases, generate an inhomogeneous concentration pattern from an initially homogeneous state and thus break the symmetry spontaneously. Such a mixture is called a reaction-diffusion (RD) system and the mechanism of symmetry-breaking receives the name of spatial instability.…”
Section: Pattern Formation By a Reactiondiffusion Turing Instabilitymentioning
confidence: 99%
“…Such a mixture is called a reaction-diffusion (RD) system and the mechanism of symmetry-breaking receives the name of spatial instability. This instability happens only under the following necessary condi- 1 For a historical perspective see ref. 3. tions:…”
Section: Pattern Formation By a Reactiondiffusion Turing Instabilitymentioning
confidence: 99%
See 2 more Smart Citations